UPAYA PENINGKATAN KEAKTIFAN DAN HASIL BELAJAR IPS DENGAN METODE PEMBELAJARAN TEAMS GAMES TOURNAMENT (TGT) DAN MEDIA TEKA TEKI SILANG PADA TEMA KERAGAMAN SOSIAL BUDAYA UNTUK SISWA KELAS VII G DI SMP N I JATEN TAHUN PELAJARAN 2014 / 2015 - Purwani, Dyah; Jobagio, Hermanu; Suryani, Nunuk (Sebelas Maret University (UNS), 2015)
The purposes of this research are to determine the increase of activeness and learning outcome of social science in grade VII G in SMP N 1 Jaten by applying Team Games Tournament learning methods and also crossword puzzle media on the theme of social cultural diversity. This research is a classroom action researches which is conducted in SMP N 1 Jaten while the object of this researches is students in grade VII G with number of 34 students consisting of 18 male and 16 female. Data collection is conducted by observation and that observation is applied for the teachers and students, the test is done on each cycle and document analysis. Researches process is carried out in three cycle including planning, implementation, observation and reflection steps. The results of this research show that: 1. the activeness of students have increased from pre-cycle to cycle 3. These results can be seen from results of observation sheets of students conducted by researchers and supported by subject teachers. Student activeness in cycle 1 is at 58.82% at the time of delivering material, then cycle 2 becomes 14.70% (5 students) and cycle 3 is (34 students/ 100%). The activeness of group activity cycle 1 is 26 (76.47%), cycle 2 is 27 (79.41%) and then cycle 3 is 100%. While, at time in doing question test cycle 1 is 2 ( 58.82%), cycle 2 is 5 (14.70%) and cycle 3 is 18 (52.94%) The conclusion of this research is that there is an increasing of activeness and student learning outcomes through the use of Teams Games Tournament methods and also crossword puzzle on the theme of social and cultural diversity in SMP N 1 Jaten academic years 2014/2015.